Effect of short curing times with a high-intensity light-emitting diode or high-power halogen on shear bond strength of metal brackets before and after thermocycling - (:unkn) unknown (E H ANGLE EDUCATION RESEARCH FOUNDATION, INC, 2011)
Objective: To test the hypothesis that short curing times using a high-intensity light-emitting diode (LED) or high-power halogen are not associated with compromised shear bond strength (SBS) of metal brackets before and after thermocycling. Materials and Methods: Two hundred forty extracted human premolar teeth were divided into six groups of 40 each. Metal brackets were bonded using a light-cured composite (Transbond XT). In group 1 a conventional halogen light (Hi lux) was used for 40 seconds. In groups 2, 3, and 4 a high-power halogen light (Swiss Master) was used for 2, 3, and 6 seconds, respectively. In groups 5 and 6 a high-intensity LED (Bluephase) was used for 10 and 20 seconds, respectively. After bonding, half of the specimens in each group were thermocycled, and all specimens were tested for SBS. After debonding, the bracket bases and the enamel surfaces were scored according to the Adhesive Remnant Index. Results: Two-way analysis of variance detected significant differences in SBS values with respect to curing method (type of light-curing unit and curing time) (P = .0001) and thermocycling (P = .01). Tukey post hoc analysis showed that with or without thermocycling the mean SBS values of groups 1, 4, 5, and 6 were not significantly different, whereas group 2 showed the lowest SBS values. The predominant failure site for groups 2 and 3 was between the bracket and the adhesive and for groups 4, 5, 6 it was at the tooth/adhesive interface. Conclusion: Curing time can be reduced to 6 seconds with high-power halogen light and to 10 seconds with high-intensity LED without compromising in vitro SBS of metal brackets. (Angle Orthod. 2011;81:510-516.)
Keywords: Light-emitting diode; Halogen; ORTHODONTIC BRACKETS; POLYMERIZATION TIMES; RESIN COMPOSITE; ADHESIVE; DENSITY; UNITS; CURE